2021
DOI: 10.3389/fphar.2021.578796
|View full text |Cite
|
Sign up to set email alerts
|

Risk Compounds, Preclinical Toxicity Evaluation, and Potential Mechanisms of Chinese Materia Medica–Induced Cardiotoxicity

Abstract: Chinese materia medica (CMM) has been applied for the prevention and treatment of diseases for thousands of years. However, arrhythmia, myocardial ischemia, heart failure, and other cardiac adverse reactions during CMM application were gradually reported. CMM-induced cardiotoxicity has aroused widespread attention. Our review aimed to summarize the risk compounds, preclinical toxicity evaluation, and potential mechanisms of CMM-induced cardiotoxicity. All relevant articles published on the PubMed, Embase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 179 publications
0
5
0
Order By: Relevance
“…Myocardial enzymes, such as cTnI, cTnT, CK-MB, LDH and AST produced in cardiomyocytes, can be released from damaged tissue into the blood circuit under pathological conditions ( Zhu et al, 2021 ). This serum myocardial zymogram can be used as a reliable index to determine the integrity of the myocardial membrane and the degree of myocardial injury ( Zhou et al, 2021 ). Combined with the observation of myocardial infarct size in rats, these results confirm the protective effect of OA on MI/RI.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial enzymes, such as cTnI, cTnT, CK-MB, LDH and AST produced in cardiomyocytes, can be released from damaged tissue into the blood circuit under pathological conditions ( Zhu et al, 2021 ). This serum myocardial zymogram can be used as a reliable index to determine the integrity of the myocardial membrane and the degree of myocardial injury ( Zhou et al, 2021 ). Combined with the observation of myocardial infarct size in rats, these results confirm the protective effect of OA on MI/RI.…”
Section: Discussionmentioning
confidence: 99%
“…The structure labeled as number 2 in this study, a rare rearranged aconitine-type C-19 diterpenoid alkaloid, showed a slight inhibitory effect (10% inhibition rate) on the expression of NRF2-regulated genes at concentration of 10 µM and therefore promoted cytotoxic activity [ 139 ]. Apart from the promising NRF2-inhibitory activity, the present research in this field is limited concerning risk factors, particularly regarding the possible cardiac toxicity [ 141 , 142 ]. Thus, future studies should focus on increasing the selectivity of the cytotoxic action on cancer cells while sparing the healthy cells.…”
Section: Plant Bioactive Compounds—alkaloids As Nrf2 Inhibitorsmentioning
confidence: 99%
“…Drugs inducing cardiotoxicity by targeting mitochondria invariably proceed to MMP collapse and mPTP opening ( Table 3 ). Antineoplastic agents, including DOX [ 73 , 81 , 164 ], As 2 O 3 [ 84 , 229 ], and imatinib [ 91 ]; β adrenergic receptor blockers, such as propranolol and atenolol [ 119 ]; antiarrhythmic drugs dronedarone and amiodarone [ 139 ]; antibiotics erythromycin and clarithromycin; NSAIDs such as naproxen, diclofenac, and celecoxib [ 60 ]; and diabetes drug pioglitazone [ 122 ] have all been reported to cause these harmful effects. mPTP opening and MMP decrease consequently induce loss of respiratory control and imbalance in ATP production, and loss of mitochondrial components such as ATP, NAD+, and glutathione, leading to water accumulation in the matrix, which causes mitochondrial osmotic swelling, IMM unfolding, and the rupture of the OMM [ 230 , 231 ].…”
Section: Main Properties Of Mitochondria and Drug-induced Mitochondri...mentioning
confidence: 99%